Understanding the Role of Forests in Enhancing Livelihoods and Climate Resilience : Case Studies in the Philippines - World Bank (World Bank, Washington, DC, 2020)
This policy brief presents the findings of a recent study focusing on two important aspects of forest ecosystems: how forest ecosystems help enhance people’s resilience to climate impacts, and how forest ecosystems support livelihood development for the poor.